Child development for child care and protection workers - Daniel, Brigid, 1959- (Jessica Kingsley Publishers, 2010)
Child Development for Child Care and Protection Workers is a classic text for students and practitioners in the child care and protection field which summarises important current thinking on child development and applies it directly to practice. The book covers key issues such as resilience and vulnerability and the impact of protective or adverse environments. Different stages of development (infancy, school age and adolescence) are discussed, and attachment theory is used to offer insights into the impact of abuse and neglect on development. A key feature is the inclusion of case studies and.